Factors Affecting User’s Intention to Adopt Smart Home in Malaysia - Wei, Ng Tee; Baharudin, Ahmad Suhaimi; A. Hussein, Lubna; Hilmi, Mohd Faiz (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Nowadays, the advancement of technology makes the life easier and convenience. Smart home is one of the technology provide a better life environment for the residents. The purpose of this study is to make a systematic and empirical study on the factors and model that influencing the intention to adopt smart home in Malaysia. Clear interface, consistency, attractiveness, information accuracy, information completeness, perceived security and perceived privacy used as the variables to investigate the intention to adopt the smart home. The quantitative method was used in this research. The sample size of this research is 102 respondents. The questionnaire was used for data collection. From the statistical analysis, the result verify that clear interface, consistency, attractiveness, information accuracy, perceived security and perceived privacy have positive impact on the Malaysian householder’s intention to adopt smart home. Besides that, the result from clustering analysis shows that, the younger generation or higher education respondents have higher intention to adopt smart home system. By referring this, the practitioner can refer and focus on those variables to develop the smart home that suitable for Malaysian.